Synopsis of the Genus Trichorondonia Breuning, 1965 with Description of a New Species from China (Coleoptera: Cerambycidae) - Ruigang Yang; Jianhua Huang; Guanglin Xie (Insects, 2025)
This paper provides a brief review of the genus Trichorondonia Breuning, 1965. A new species, Trichorondonia wenkaii sp. nov. (文凯毛郎氏天牛), is described and illustrated. Trichorondonia kabateki Viktora, 2024 is newly recorded in Hubei province, with the first description of the male. Additionally, photographs of the holotypes of three previously described species are presented. A key to the four species is given. The new species differs from T. pilosipes and T. hybolasioides in having elytra with rounded lateral apical angles and a vertex with blackish-brown pubescence medially behind the eyes. The new species can also be easily distinguished from T. kabateki by the antennae being ventrally fringed with sparse hairs only on segments 1–8, the greyish-yellow pubescence on the pronotum being unevenly distributed and particularly sparse in the posterior half, the elytra having rather thin greyish-yellow pubescence and hardly visible greyish-white pubescence, elongated blackish-brown spots on the elytral longitudinal carinae, and a small tuft of black setae at the centre of the elytral base where there is no obvious tubercle. The type specimen of the new species was collected in Dianping village, Xinhua town, Leye county, Guangxi Zhuang Autonomous Region of China, and deposited at Insect Collection, College of Agriculture, Yangtze University, Jingzhou, Hubei, China (ICYZU).